Musculoskeletal trauma simplified a casebook to aid diagnosis and management - Diwan, Amna (TFM Pub., 2009)
Presents a simple case-by-case approach to the many different types of orthopaedic fractures. This book is divided into sections by anatomic location, each containing a number of cases presented as unknowns. A standard template is utilised for each case, including a brief clinical description, physical examination, followed by radiological images.